ANALYSIS AND SOLUTIONS FOR DECREASING THE EFFECTIVENESS OF THE AIR CONDITIONING SYSTEM ON THE BOEING 737-900 ER - Ristiawan, Bayu Ristiawan; Wicaksono, Dhimas (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
The air conditioning system on the Boeing 737-900 ER plays a crucial role in maintaining passenger and cabin crew comfort. However, a decrease in the system’s effectiveness has led to discomfort during flights. This study aims to identify the factors causing the decline in the air conditioning system’s effectiveness and provide technical recommendations to enhance its performance. The research method used is Root Cause Analysis (RCA) with a Failure Mode and Effects Analysis (FMEA) approach. The findings indicate that the primary causes of decreased AC system effectiveness are blockages in the heat exchanger due to debris accumulation and oil contamination, as well as damage to the Air Cycle Machine (ACM), including worn-out turbine blades and bearings. To address these issues, preventive maintenance procedures, routine inspections, and the use of an air conditioning cart while the aircraft is on the ground are recommended to maintain cabin comfort.